Phân tích đa thức thành nhân tử: a,9(x+5)^2-(x-7)^2 b,25-(3-x)^2 c,(7x-4)^2-(2x+1)^2 d,9(x+1)^2-1 13/08/2021 Bởi Melody Phân tích đa thức thành nhân tử: a,9(x+5)^2-(x-7)^2 b,25-(3-x)^2 c,(7x-4)^2-(2x+1)^2 d,9(x+1)^2-1
Đáp án: Giải thích các bước giải: $a,9(x+5)^2-(x-7)^2$ $=3^2(x+5)^2-(x-7)^2$ $=(3x+15)^2-(x-7)^2$ $=(3x+15-x+7)(3x+15+x-7)$ $=(2x+22)(4x+8)$ $=8(x+11)(x+2)$ $b,25-(3-x)^2$ $=5^2-(3-x)^2$ $=(5-3+x)(5+3-x)$ $=(2+x)(8-x)$ $c,(7x-4)^2-(2x+1)^2$ $=(7x-4-2x-1)(7x-4+2x+1)$ $=(5x-5)(9x-3)$ $=5(x-1)3(3x-1)$ $=15(x-1)(3x-1)$ $d,9(x+1)^2-1$ $=(3x+3)^2-1$ $=(3x+3-1)(3x+3+1)$ $=(3x+2)(3x+4)$ Chúc em học tốt. Bình luận
Đáp án:
Giải thích các bước giải:
Đáp án:
Giải thích các bước giải:
$a,9(x+5)^2-(x-7)^2$
$=3^2(x+5)^2-(x-7)^2$
$=(3x+15)^2-(x-7)^2$
$=(3x+15-x+7)(3x+15+x-7)$
$=(2x+22)(4x+8)$
$=8(x+11)(x+2)$
$b,25-(3-x)^2$
$=5^2-(3-x)^2$
$=(5-3+x)(5+3-x)$
$=(2+x)(8-x)$
$c,(7x-4)^2-(2x+1)^2$
$=(7x-4-2x-1)(7x-4+2x+1)$
$=(5x-5)(9x-3)$
$=5(x-1)3(3x-1)$
$=15(x-1)(3x-1)$
$d,9(x+1)^2-1$
$=(3x+3)^2-1$
$=(3x+3-1)(3x+3+1)$
$=(3x+2)(3x+4)$
Chúc em học tốt.